Suitability of Various Materials for Probes in Scanning Kelvin Probe Measurements. Issue 15 (11th December 2017) - Huber, Silvia; Wicinski, Mariusz; Hassel, Achim Walter
Abstract : Volta potential of a material can be easily determined by using scanning Kelvin probe (SKP), but up to now there is no standard method established. This study focuses on finding an alternative or even a standard material for SKP probes. Re, Ni, and Mo are analyzed regarding their suitability for serving as tips in SKP measurements. For comparison purposes, a commonly used NiCr probe is analyzed too. Linearity, the sensitivity to humidity changes as well as the lateral and Volta potential resolution are determined for various probe materials. Linearity is excellent for all tested probes. SKP measurements carried out under humidity variations shows dissimilar results for all different metal probes. Lateral and Volta potential resolution are the best for Re and Ni tips. There may be a correlation between the work function of a material and its suitability for serving as a probe in Kelvin measurements − the higher the work function, the better the resolution of Volta potentials. Based on the results, it can be concluded that pure Re and Ni are more suitable for serving as SKP probes than NiCr alloy. Abstract : In the present study several materials, namely Re, Ni, and Mo, are tested regarding their suitability for serving as probes in scanning Kelvin probe (SKP) measurements. For comparison purposes NiCr, a commonly used standard material, is also tested. The metals are found to be more suitable than the NiCr alloy probe. High work function of probe materials results in high resolution capacity of Volta potential.